Mitochondrial Oxidative Capacity In Human Skeletal Muscle: Association with Plasma Lactate Concentration - Cook, Jessica (East Carolina University, 2018)
ABSTRACT Background: Metabolic disease is a growing concern for public health. Obesity and Type II Diabetes are an epidemic and a phenotype for insulin resistance in human skeletal muscle. A reduced mitochondrial function and oxidative capacity may be associated with impairments in fatty acid oxidation, which can lead to insulin resistance and metabolic dysfunction. While reductions in mitochondrial content may be a predictive variable, reductions in mitochondrial proteins and an increase in peroxisomal proteins may be contributing factors to increases in FAO and reductions in mitochondria oxidation. Furthermore, due to these reductions, a shift to anaerobic glycolysis has resulted in an increase in plasma lactate concentrations. Purpose: The purpose of this study was to determine if a reduced skeletal muscle mitochondrial oxidative capacity was due to a reduction in mitochondrial content. The main aim was to look at the association between mitochondrial protein content and plasma lactate levels. A subaim of this study was to investigate peroxisomal protein content in skeletal muscle to determine if this organelle is upregulated. Methods: This study used data from a previous Johnson & Johnson study. Premenopausal women (n=44), over the age of 21 were recruited. These subjects were separated by BMI, non-obese [less than]30kg/m2, obese [greater-than or equal to]30 mg/m2 and diabetic.. Following a muscle biopsy procedure, plasma lactate concentration was determined using a Coulter-Beckman clinical blood analyzer. Mitochondrial and peroxisomal protein content was determined and analyzed using Western Blot technique Results: Mitochondrial protein content, COXIV, was significantly higher in non-obese subjects compared to obese and diabetic. Peroxisomal protein content, PEX19, was also significantly higher in diabetic subjects compared to non-obese and obese. A significant (P[less than]0.05) correlation was found between PEX19 and lactate (p[less than]0.0344). There was a significant, positive correlation between FAO and lactate in non-obese subjects (p[less than]0.0471). There was a significant difference in PMP70 protein content following a two-tailed t-test, and COXIV vs lactate following the Grubbs Test for outliers. There was no significance found between PMP70 vs lactate, COXIV vs FAO or PEX19 vs COXIV . Conclusion: Mitochondrial protein content was significantly reduced in obese and diabetic subjects with an upregulation of some peroxisomal proteins. Lactate was negatively associated with a reduced mitochondrial oxidative capacity. More research is needed to look at differences between protein content expression and the degree of adiposity.
Keywords: Mitochondrial Oxidative Capacity; Lactate; Obesity; Non-insulin-dependent diabetes; Mitochondria--Physiology; Insulin resistance; Musculoskeletal system